2011
DOI: 10.1139/h10-073
|View full text |Cite
|
Sign up to set email alerts
|

A peripheral governor regulates muscle contraction

Abstract: Active skeletal muscles are capable of keeping the global [adenosine triphosphate (ATP)] reasonably constant during exercise, whether it is mild exercise, activating a few motor units, or all-out exercise using a substantial mass of muscle. This could only be accomplished if there were regulatory processes in place not only to replenish ATP as quickly as possible, but also to modulate the rate of ATP use when that rate threatens to exceed the rate of ATP replenishment, a situation that could lead to metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 76 publications
1
28
1
2
Order By: Relevance
“…Since physiological catastrophes can and do occur [1] and a variety of peripheral factors can impair muscle performance [69], it is suggested that the proposed dominant governor could at least be over-ridden. MacIntosh and Shahi [70] proposed a peripheral governor, working at the cellular level, which can reduce the muscle contraction by attenuating activation to avoid metabolic catastrophe. Marcora [71] suggested that deciding when to terminate exercise is done by the conscious brain without the need to include an additional subconscious entity.…”
Section: From Perception To Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since physiological catastrophes can and do occur [1] and a variety of peripheral factors can impair muscle performance [69], it is suggested that the proposed dominant governor could at least be over-ridden. MacIntosh and Shahi [70] proposed a peripheral governor, working at the cellular level, which can reduce the muscle contraction by attenuating activation to avoid metabolic catastrophe. Marcora [71] suggested that deciding when to terminate exercise is done by the conscious brain without the need to include an additional subconscious entity.…”
Section: From Perception To Actionmentioning
confidence: 99%
“…However, the location of-and processes occurring associated with this controller are not understood yet. Different mechanisms are suggested at muscular level [70] as well as within the brain [64].…”
Section: The Selection Of An Appropriate Pacing-strategymentioning
confidence: 99%
“…We have proposed that the cellular regulation of ATP use is the principal mechanism for the decreased contractile response that is associated with acute repetitive muscle use, typically called muscle fatigue (MacIntosh and Shahi, 2011). We also have recognized that regulating Ca 2+ release from the sarcoplasmatic reticulum (SR), and thus the intracellular Ca 2+ concentration ([Ca 2+ ] i ), dictates the rate of ATP use in the muscle cell because it affects Ca 2+ ATPase and myosin ATPase activity, which together account for 90% of ATP use (Box 1).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the AT is an indirect procedure to determine the aerobic endurance and not always leads to exhaustion, while the time to exhaustion at this intensity (tlim) is adopted as a direct procedure (5). The motives of exhaustion at AT has been investigated since the 1920s, and owing the diffi culty caused by multi factorial characteristic, are still actively researched today (6). Some authors have associated the inability to continue exercise at aerobic required intensity to a lack of energetic substrates, mainly glycogen depletion (7,8).…”
mentioning
confidence: 99%